PV-Battery Powered Direct Torque Controlled Switched Reluctance Motor Drive - Ronanki, D.; Parthiban, P. (2012 Asia-Pacific Power and Energy Engineering Conference, 2012)
Categorized as one of the renewable energies, Photo-Voltaic system has a great potential compared to its counterparts of renewable energies. This paper deals with the design of a Photovoltaic (PV)-Battery fed Switched Reluctance Motor(SRM). The system mainly composed of a PV module, boost converter, rechargeable battery, bidirectional converter, asymmetric bridge converter, SRM and system controllers. The main problems of SRM are high torque ripple, acoustic noise and vibration problems. In order to reduce these problems, a new direct torque control of 3.5 kW 8/6 SRM is proposed, which is simple and can be implemented with low cost processor. It can be seen from the simulation results that this scheme has well regulated the torque output of the motor with in hysteresis band. The proposed system assures its suitability for solar applications like solar vehicles, solar water pumping system and floor mills in hilly and isolated areas.